Journeys of black women in academe : shared lessons, experiences, and insights - Walker, Brenda L. (Diversity in higher education, 2024)
What advice or lessons learned would you want seasoned Black women in academe to impart to early and mid-career women faculty, researchers, and administrators of color, especially those of African descent? This book is composed of narratives from Black American women professors who have been in higher education for at least two decades. Despite all challenges and obstacles, these scholars have enjoyed successful careers in the Academy. They share reflections on critical incidents and select lessons that they experienced and learned from throughout their accomplished careers. In this book, academic wisdom aligns with ancestral wisdom to benefit emerging scholars, faculty, and administrators in academia. Journeys of Black Women in Academe provides lessons that are instructive to faculty and administrators across race and gender boundaries relative to the successes and challenges that African American women continue to experience in academia.